Choosing the appropriate neonatal resuscitation device for village midwives. - Ariawan, I; Agustini, M; Seamans, Y; Tsu, V; Kosim, M S (Journal of Perinatology, 2011)
Objective:An appropriate neonatal resuscitation device for village midwives in Indonesia is chosen.Study Design:The study compared four neonatal resuscitation devices: Ambu neonate bag and mask, Topster bag and mask, Laerdal pediatric pocket mask and Tekno tube and mask. Functionality was tested by 40 village midwives who were also interviewed about ease of use. Ventilation volume was tested using a mannequin and computer interface. Other features were assessed by PATH engineers.Result:There was no significant difference in the ventilation volumes among the four devices or any difference in acceptability to midwives or infection prevention ability, but the tube and mask devices were considered easier to clean.Conclusion:Given the similarity in functionality, ease of use, infection prevention, and portability and the significant difference in price, public health experts and neonatologists chose the local tube and mask device for use by village midwives.